Mechanism of association between BMI and dysfunction of the gastro-oesophageal barrier in patients with normal endoscopy. Issue 3 (28th August 2011) - Derakhshan, Mohammad H; Robertson, Elaine V; Fletcher, Jonathan; Jones, Gareth-Rhys; Lee, Yeong Yeh; Wirz, Angela A; McColl, Kenneth E L
Abstract : Introduction: The association between body mass index (BMI) and gastro-oesophageal pressure gradient (GOPG) is incompletely understood. We examined the association between BMI and gastro-oesophageal (GO) barrier function and the effect of mechanically increasing intra-abdominal pressure on GO physiology. Methods: (A) 103 dyspeptic patients with normal endoscopy underwent 24 h pH-metry and upper gastrointestinal manometry. Relationships between BMI and acid reflux, intragastric pressure (IGP), GOPG and lower oesophageal sphincter (LOS) pressure were calculated using bivariate correlations. (B) In 18 healthy volunteers, the effects of increasing IGP by abdominal belt on GO manometry were studied. Results: (A) There was a linear correlation between BMI and oesophageal acid exposure in erect (R=0.35, p<0.001) and supine (R=0.40, p<0.001) positions. BMI was strongly associated with IGP (inspiration: R=0.66, p<0.001; expiration: R=0.78, p<0.001) and inspiratory GOPG (R=0.50, p<0.001). There were a positive correlation between BMI and inspiratory LOS pressure relative to atmospheric pressure (R=0.29, p=0.016) and a negative correlation with LOS pressure relative to IGP on expiration (R=−0.25, p=0.018). Logistic regression models using all significant manometric variables and relevant interactions revealed marked decline in the magnitude and significance of relationship between BMI and oesophageal acid exposure in supine (from OR 1.12 (95% CI 1.03 to 1.22), p=0.009, to 1.00 (0.86 to 1.17), p=0.999) and upright positions (from 1.11 (1.02 to 1.20), p=0.020, to 1.03 (0.89 to 1.18), p=0.717). (B) Application of the constricting abdominal belt produced similar manometric changes to those associated with increased BMI. However, the belt did not reproduce the reduced LOS pressure relative to IGP. Conclusion: The association between reflux and BMI may be largely explained by effects of increased intra-abdominal pressure. However, the reduced LOS pressure associated with BMI may be mediated by another mechanism or effects of chronic rather than acute elevation of intra-abdominal pressure.